Study on reducing the risk of stress corrosion cracking of austenitic stainless steel hydraulically expanded joints. (July 2020) - Hong, Ying; Wang, Xuesheng; Wang, Yan; Zhang, Zhao
Highlights: The cause of failure of 304L hydraulically expanded joints was analyzed. A feasible method to reduce the SCC risk of 304L expanded joints was proposed. The synthetic consideration of expansion parameters was put forward. This study offers a reference for the hydraulically expanded joints manufacturing. Abstract: Stress corrosion cracking (SCC) is one of the main failure modes of tube-to-tubesheet expanded joints in tubular heat exchangers, and the residual tensile stress is an important factor in the development of these cracks. Many tubular heat exchangers in nuclear-power stations are made of 304L stainless steel, and SCC often occurs in the tube-to-tubesheet expanded joints during service. However, few studies on the failure analysis of these expanded joints of 304L stainless steel have been reported. In this paper, the residual stresses in the hydraulically expanded joints of a high-pressure heater used in one nuclear-power station were evaluated by the finite element method (FEM) to reveal the cause of crack formation. Meanwhile, the effects of the expansion pressure and yield strength on the residual stress of 304L tubes in the expanded joint were studied by the FEM and SCC tests. The FEM results showed that the residual stress of the tube in the expanded zone decreased with the increase in the expansion pressure. But the maximum residual stress, which was located at the transition zone between the expanded and unexpanded zone of the joint, was not affected by the expansion pressure. The yield strength of the tube had a significant influence on the residual stress in the hydraulically expanded joint. Reducing the yield strength of the tube could reduce the maximum residual tensile stress to reduce the risk of SCC. The FEM results were in good agreement with the SCC test results, which were performed following the Design and Construction Rules for Mechanical Components of PWR Nuclear Islands (RCC-M). This study provides a basis for the manufacturing process of austenitic stainless-steel tube-to-tubesheet hydraulically expanded joints.